2018
DOI: 10.1038/s41431-018-0152-0
|View full text |Cite
|
Sign up to set email alerts
|

Carrier frequency analysis of mutations causing autosomal-recessive-inherited retinal diseases in the Israeli population

Abstract: Inherited retinal diseases (IRDs) are heterogeneous phenotypes caused by variants in a large number of genes. Disease prevalence and the frequency of carriers in the general population have been estimated in only a few studies, but are largely unknown. To this end, we developed two parallel methods to calculate carrier frequency for mutations causing autosomal-recessive (AR) IRDs in the Israeli population. We created an SQL database containing information on 178 genes from gnomAD (including genotyping of 5706 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
0
8
1
Order By: Relevance
“…In most of these families, the single identified allele is probably causative, and the second allele has been missed due to technical reasons (lack of coverage, inaccurate annotation, nonexonic localization, inability to pick up the genetic defect, or inaccurate interpretation). However, it should be noted that some IRD causative mutations have a very high carrier frequency in the Israeli population, and therefore, IRD patients may be coincidental carriers of these mutations, in addition to the mutations which are actually causing their disease (Hanany et al, ). It is therefore not surprising that in 6% (79/1,368) of solved families, we identified a heterozygous disease‐causing mutation in another IRD gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these families, the single identified allele is probably causative, and the second allele has been missed due to technical reasons (lack of coverage, inaccurate annotation, nonexonic localization, inability to pick up the genetic defect, or inaccurate interpretation). However, it should be noted that some IRD causative mutations have a very high carrier frequency in the Israeli population, and therefore, IRD patients may be coincidental carriers of these mutations, in addition to the mutations which are actually causing their disease (Hanany et al, ). It is therefore not surprising that in 6% (79/1,368) of solved families, we identified a heterozygous disease‐causing mutation in another IRD gene.…”
Section: Discussionmentioning
confidence: 99%
“…Such mutations are frequent among affected individuals from the same ethnic group. The Arab population is characterized by a high rate of consanguinity, leading to increased homozygosity of rare mutant alleles in specific families and villages (Hanany et al, ; Zlotogora, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the involvement of ZNF513 and INPP5E in IRD is reported only in Pakistani and European populations respectively [134]. Population specific founder mutations have also been reported [135]. Our previous studies on Pakistani population identified p.Pro363Thr variant in RPE65 that is specific to the South Asian population as the common causative mutation [7,92].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…For CF and pGP analysis, only heterozygous PLPV (not homozygous PLPV) was considered [14][15][16]. Therefore, the allele frequency of heterozygous PLPV (AF V ) and CF V for a variant V were calculated as follows:…”
Section: Carrier Frequency (Cf) and Predicted Genetic Prevalence Analysis (Pgp)mentioning
confidence: 99%